2018
DOI: 10.18608/jla.2018.51.2
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Approach to Analyze Shared Epistemic Agency in Jigsaw Instruction at Multiple Scales of Temporality

Abstract: The purpose of this study was to propose a mixed-methods approach to analyzing shared epistemic agency in jigsaw instruction from multiple temporal perspectives, and to evaluate its effectiveness by examining actual datasets. We employed a combination of socio-semantic network analysis (SSNA) and in-depth dialogical discourse analysis as a mixed-methods approach, and analyzed discourse transcripts by university students engaged in jigsaw instruction. First, we graphically depicted a quantitative measure of sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Previous research has revealed the significance of shared epistemic agency in knowledge‐related collaborative inquiry (eg, Lei & Chan, ; Oshima et al , ; Yang, ), and some studies have demonstrated the positive effects of high‐level shared epistemic agency on domain understanding (Yang, ; Yang et al , ; Zhang et al , ), the productivity of collaboration (Damşa, ), collective knowledge advancements (Oshima et al , ; Yang, ), and the development of high‐level competences among students (Borge et al , ; Chen, ; Yang, ). Shared epistemic agency is essential for sustaining collaborative efforts to pursue knowledge advancement (Damşa et al , ; Scardmalia, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has revealed the significance of shared epistemic agency in knowledge‐related collaborative inquiry (eg, Lei & Chan, ; Oshima et al , ; Yang, ), and some studies have demonstrated the positive effects of high‐level shared epistemic agency on domain understanding (Yang, ; Yang et al , ; Zhang et al , ), the productivity of collaboration (Damşa, ), collective knowledge advancements (Oshima et al , ; Yang, ), and the development of high‐level competences among students (Borge et al , ; Chen, ; Yang, ). Shared epistemic agency is essential for sustaining collaborative efforts to pursue knowledge advancement (Damşa et al , ; Scardmalia, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Collaborative inquiry, nowadays a major research strand in education, can help students to develop these future‐ready competences, such as inquiry, collaboration, knowledge creation, agency and metacognition. However, the development of these competences relies heavily on students' enactment of high‐level shared epistemic agency (Damşa, ; Oshima, Oshima, & Fujita, ; Rappa & Tang, ; Scardamalia & Bereiter, ; Zhang et al , ). This is problematic because many students exhibit little shared epistemic agency in collaborative inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies on learning as knowledge creation have been conducted by applying qualitative approaches, it is needed to develop a new quantitative analytic framework for evaluating learning as a knowledge creation practice to handle larger and richer datasets (Martinez et al, 2003;Scardamalia et al, 2012). Both qualitative and quantitative analyses are expected to provide us with deeper insights into student learning in the mixed-methods approach (Johnson and Onwuegbuzi, 2006;Oshima et al, 2018). A promising quantitative approach that recent studies have discussed is socio-semantic network analysis (SSNA).…”
Section: Evaluation Of Learning As Knowledge Creationmentioning
confidence: 99%
“…Through visualizing the network structure of words or codes used in discourse, researchers could represent how a group of learners engage in their knowledge creation. The SSNA approach has been adopted in educational studies to analyze rotation of leadership among students in the knowledge-building community (e.g., Ma et al, 2016) and to detect productive interaction patterns in the knowledge-creation practice, such as in the jigsaw instruction (e.g., Oshima et al, 2018).…”
Section: Evaluation Of Learning As Knowledge Creationmentioning
confidence: 99%
“…A study of communal knowledge in online knowledge building discourse used temporal analytics combined with graph theory to identify ideas and their mobility over time 22 . Graph centrality has been used to explore temporal and contextual profiles of shared epistemic agency on discourse transcripts 23 , identifying pivotal points of discourse exchanges. One study emphasised the importance of temporality as the main component of learning analytics through main path analysis of Wikiversity domains to model the flow of ideas 24 .…”
Section: Introductionmentioning
confidence: 99%